Chemotherapy for Pancreatic Cancer can be Optimized with the Use of Drug Resistance Testing Using Tissue Organoids - Gul Mehnaz, Tariq Mehmood Khan, Salma Rasheed Khan, Asma Shaukat, Abdul Haseeb, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The purpose of the present investigation was to ascertain how drug resistance in pancreatic cancer organoids affects the efficacy of chemotherapy. Study Design: Retrospective study Place and Duration: Jinnah International hospital, Abbottabad, 15th March- 15th September, 2022 Methods: A total of 72 patients of both genders with pancreatic cancer were presented in this study. After obtaining written consent from participants, we recorded detailed demographic information about them, including their age, sex, and body mass index. Pathological evaluation of tumour regression grade (TRG) was compared to data on the dose and schedule of neoCTx treatment. SPSS 22.0 was used to analyze all data. Results: This study had 43 (59.7%) males and 29 (40.3%) females. 22 (30.6%) patients were aged between 18-30 years, 25 (34.7%) patients had aged between 31-40 years, 15 (20.8%) patients had aged 41-50 years, and 10 (13.9%) patients had aged> 50 years. In a study with 15 CTx-naive PDO lines, 8 showed a distinct response to FOLFIRINOX or Gem/Pac. As much as 34.7 per cent of patients with NeoCTx PDOs experienced an unfavorable reaction to their neoadjuvant treatment. Modified treatments in which the lowest successful individual medicine was eliminated from the full regimen showed no meaningful change in PDO response. Conclusion: It is possible that drug testing on CTx-nave PDAC PDOs and neoCTx PDOs will help determine the optimal neoadjuvant and adjuvant treatment regimens. In order to increase the proportion of patients completing the course of neoadjuvant treatment, it may be beneficial to individualize poly-chemotherapy regimens by removing chemicals with low effectiveness. Keywords: Pancreatic Cancer, Chemotherapy, Drug Resistance, Tissue Organoids